EVALUASI SENSORI KEFIR AIR KELAPA HIJAU DENGAN BERBAGAI KONSENTRASI GULA KELAPA - Panjaitan, Pritania Selena; Raharjo, Dwi; Kusuma Dewi, Yohana Sutiknyawati (Fakultas Pertanian Universitas Tanjungpura, 2025)
This study aims to evaluate the sensory characteristics of green coconut water kefir with the addition of various concentrations of coconut sugar. The concentrations tested were 0%, 5%, 10%, 15%, and 20%. A total of 30 untrained panelists participated in the sensory evaluation, which was conducted descriptively based on four attributes: aroma, taste, color, and overall preference. The results showed that coconut sugar concentration significantly affected the sensory quality of the kefir. The 20% concentration produced the highest scores in aroma (4.17), taste (3.60), and color (4.80), indicating a stronger coconut sugar aroma, more pronounced sourness, and a darker brown appearance. However, the highest overall preference was observed at the 15% concentration, with a score of 4.20, suggesting that this level was most acceptable to the panelists. It can be concluded that while 20% coconut sugar enhances certain sensory attributes, the 15% concentration provides the best balance between flavor, appearance, and consumer acceptability. These findings can support further development of coconut water kefir as a functional fermented beverage with desirable sensory quality.